Synthesis of rGO-TiO2 Composite for Al-ion Battery with Enhanced Electrical Conductivity - Afian, Ruli; Faizal, Ferry; Panatarani, Camellia; Joni, I Made (The Physical Society of Indonesia, 2025)
Alternative batteries to lithium-ion are attracting growing attention due to the urgent demand for high energy density and limited lithium resources. Aluminum-ion (Al-ion) batteries are promising since aluminum is abundant, recyclable, and inexpensive. They also provide theoretically high specific energy and power through a three-electron redox reaction. However, challenges remain because no positive electrode material has yet shown efficient and reversible aluminum-ion storage. This study reports the synthesis of a reduced graphene oxide–titanium dioxide (rGO–TiO₂) composite and its evaluation as an electrode for Al-ion batteries. The rGO–TiO₂ composites were prepared by hydrothermal reaction with TiO₂ contents of 2, 5, and 10 wt.%. Characterization using X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) confirmed that graphite oxide (GO) was successfully reduced to rGO, as indicated by a peak at 2θ = 24.30°. Electrochemical testing of rGO–TiO₂ based Al-ion batteries showed improved ion diffusivity of 1.39 × 10⁻⁶ – 3.83 × 10⁻⁶ cm/s and charge–discharge capacities of 6.9–7.2 mAh/g at 1C (0.1–0.3 mA·g⁻¹). These results demonstrate the key role of enhanced ion diffusivity in advancing high-performance Al-ion batteries.